2008
DOI: 10.4049/jimmunol.181.12.8604
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR9 Synergistically Control Herpes Simplex Virus Infection in the Brain

Abstract: Viruses are recognized by the innate immune system through pattern recognition receptors (PRRs). For instance, HSV virions and genomic DNA are recognized by TLR2 and TLR9, respectively. Although several viruses and viral components have been shown to stimulate cells through TLRs, only very few studies have defined essential roles for single TLRs in innate immune defense in vivo. This could suggest that PRRs act in concert to mount the first line of defense against virus infections. To test this hypothesis we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
165
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(172 citation statements)
references
References 61 publications
5
165
0
2
Order By: Relevance
“…In the case of HSV this appears to be the case. TLR2 detects an unknown molecule from the HSV viron, while TLR9 detects CpG [97]. Consequently it has been found that TLR2 and TLR9 function synergistically to respond to HSV infection in the brain [97].…”
Section: Tlrs and Herpes Simplex Encephalitismentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of HSV this appears to be the case. TLR2 detects an unknown molecule from the HSV viron, while TLR9 detects CpG [97]. Consequently it has been found that TLR2 and TLR9 function synergistically to respond to HSV infection in the brain [97].…”
Section: Tlrs and Herpes Simplex Encephalitismentioning
confidence: 99%
“…TLR2 detects an unknown molecule from the HSV viron, while TLR9 detects CpG [97]. Consequently it has been found that TLR2 and TLR9 function synergistically to respond to HSV infection in the brain [97]. HSV loads in the brain were found to be greater in the TLR2/9 double knockouts compared with brains from either the single knockouts.…”
Section: Tlrs and Herpes Simplex Encephalitismentioning
confidence: 99%
See 2 more Smart Citations
“…TLR7 regulates the innate immune response to retrovirus and West Nile virus infections of the CNS, and TLR9 has been implicated in mediating the innate immune response to herpes simplex virus infection in the brain. [12][13][14][15][16] TLR7 and TLR9 agonists have been analyzed for their potential use in the therapeutic treatment of CNS maladies from glioblastomas to viral infection. However, responses to stimulation of these receptors in the CNS often differ, particularly in neonates.…”
mentioning
confidence: 99%